Nutritional Status of Mediterranean Trees Growing in a Contaminated and Remediated Area - Domínguez, MaríaT; Marañón, Teodoro; Murillo, JoséM; Schulin, Rainer; Robinson, BrettH (Water, Air, and Soil Pollution, 2010)
t Soil contamination may contribute to forest decline, by altering nutrient cycling and acquisition by plants. This may hamper the establishment of a woody plant cover in contaminated areas, thus limiting the success of a restoration program. We studied the nutritional status of planted saplings of Holm oak (Quercus ilex subsp. ballota (Desf.) Samp.), white poplar (Populus alba L.), and wild olive tree (Olea europaea var. sylvestris Brot.) in the Guadiamar Green Corridor (SW Spain) and compared it with established adult trees. Soils in this area were affected by a mine-spill in 1998 and a subsequent restoration program. The spill resulted in soil acidification, due to pyrite oxidation, and deposited high concentrations of some trace elements. In some sites, we detected a phosphorus deficiency in the leaves of Q. ilex and O. europaea saplings, as indicated by a high N:P ratio (>16). For O. europaea, soil contamination explained 40% of the variability in leaf P and was negatively related to chlorophyll content. Soil pH was a significant factor predicting the variability of several nutrients, including Mg, P, and S. The uptake of Mg and S by P. alba was greater in acidic soils. The monitoring of soil pH is recommended since long-term effects of soil acidification may negatively affect the nutritional status of the trees
The following values have no corresponding Zotero field: publisher: Springer Netherlands
Keywords: Heavy metal; Olea europaea; phosphorus; Populus alba; Quercus ilex; soil remediation; Tree nutrition

Trace element accumulation in woody plants of the Guadiamar Valley, SW Spain: a large-scale phytomanagement case study. - Domínguez, María T.; Marañón, Teodoro; Murillo, José M.; Schulin, Rainer; Robinson, Brett H. (Environmental pollution (Barking, Essex : 1987), 2008)
Phytomanagement employs vegetation and soil amendments to reduce the environmental risk posed by contaminated sites. We investigated the distribution of trace elements in soils and woody plants from a large phytomanaged site, the Guadiamar Valley (SW Spain), 7 years after a mine spill, which contaminated the area in 1998. At spill-affected sites, topsoils (0-25 cm) had elevated concentrations of As (129 mg kg(-1)), Bi (1.64 mg kg(-1)), Cd (1.44 mg kg(-1)), Cu (115 mg kg(-1)), Pb (210 mg kg(-1)), Sb (13.8 mg kg(-1)), Tl (1.17 mg kg(-1)) and Zn (457 mg kg(-1)). Trace element concentrations in the studied species were, on average, within the normal ranges for higher plants. An exception was white poplar (Populus alba), which accumulated Cd and Zn in leaves up to 3 and 410 mg kg(-1) respectively. We discuss the results with regard to the phytomanagement of trace element contaminated sites.
The following values have no corresponding Zotero field: accession-num: 17602809
Keywords: Bioaccumulation; biodegradation; Environmental; Environmental Monitoring; Environmental Monitoring: methods; Heavy; Heavy metal; Heavy: analysis; Mass spectrometry; metals; Mining; Olea; Olea europaea; Olea: chemistry; Phytoremediation; Plant Leaves; Plant Leaves: chemistry; Populus; Populus alba; Populus: chemistry; Quercus; Quercus ilex; Quercus: chemistry; Soil; Soil Pollutants; Soil Pollutants: analysis; Soil: analysis; Spain; Species Specificity

Trace element accumulation in woody plants of the Guadiamar Valley, SW Spain: a large-scale phytomanagement case study. - Domínguez, María T; Marañón, Teodoro; Murillo, José M; Schulin, Rainer; Robinson, Brett H (Environmental pollution (Barking, Essex : 1987), 2008)
Phytomanagement employs vegetation and soil amendments to reduce the environmental risk posed by contaminated sites. We investigated the distribution of trace elements in soils and woody plants from a large phytomanaged site, the Guadiamar Valley (SW Spain), 7 years after a mine spill, which contaminated the area in 1998. At spill-affected sites, topsoils (0-25 cm) had elevated concentrations of As (129 mg kg(-1)), Bi (1.64 mg kg(-1)), Cd (1.44 mg kg(-1)), Cu (115 mg kg(-1)), Pb (210 mg kg(-1)), Sb (13.8 mg kg(-1)), Tl (1.17 mg kg(-1)) and Zn (457 mg kg(-1)). Trace element concentrations in the studied species were, on average, within the normal ranges for higher plants. An exception was white poplar (Populus alba), which accumulated Cd and Zn in leaves up to 3 and 410 mg kg(-1) respectively. We discuss the results with regard to the phytomanagement of trace element contaminated sites.
Keywords: Bioaccumulation; biodegradation; Environmental; Environmental Monitoring; Environmental Monitoring: methods; Heavy; Heavy metal; Heavy: analysis; Mass spectrometry; metals; Mining; Olea; Olea europaea; Olea: chemistry; Phytoremediation; Plant Leaves; Plant Leaves: chemistry; Populus; Populus alba; Populus: chemistry; Quercus; Quercus ilex; Quercus: chemistry; Soil; Soil Pollutants; Soil Pollutants: analysis; Soil: analysis; Spain; Species Specificity

EVOLUCIÓN TEMPORAL DEL GRADO DE ENDURECIMIENTO DE PLANTAS DE VIVERO DE 4 ESPECIES FORESTALES ESPAÑOLAS CULTIVADAS EN LOCALIDADES CON CONDICIONES CLIMÁTICAS DISTINTAS - Fernández, M; Carvajal, F; Alejano, R; Domínguez, L; TAPIAS, R; Alesso, S P (IV Congreso Forestal Español, 2005)
Desde principio del otoño hasta principio de primavera se estudió la evolución de algunos caracteres morfo-fisiológicos indicadores de la calidad de las plantas de vivero destinadas a repoblación forestal (altura, diámetro, distribución de biomasa, nutrición mineral, capacidad de regeneración de raíces y resistencia al frío). Las especies ensayadas fueron Quercus suber, Q. ilex (de dos regiones de procedencia, 11e y 15a), Pistacia lentiscus y Olea europaea var. sylvestris. Todas ellas eran de una savia, procedentes de semillas germinadas en la primavera anterior, crecidas en el mismo tipo de envase (300 cm3) y con el mismo substrato pero cultivadas en dos viveros de localización y características climáticas diferentes. En cuanto al patrón de evolución temporal de los parámetros medidos, se advirtió una alta correlación con la temperatura ambiente, siendo el vivero de clima con estaciones más marcadas el que alcanzó con anterioridad su grado máximo de resistencia al frío y el que retrasó la salida de la dormición durante la época invierno-primavera. Indudablemente, las distintas especies se diferenciaron en su patrón de evolución y en el grado de resistencia al frío conseguido, debiendo resaltar las diferencias encontradas entre las dos procedencias de encina, siendo la de clima con estaciones más extremas (15a) la que en todo momento presentó un mayor grado de resistencia al frío. También se encontró un alto grado de correspondencia entre el contenido en K y la resistencia al frío o el contenido en N y P con la capacidad de regeneración de raíces. Las cuatro especies necesitaron acumular, al menos, 350 h (< 8 ºC) para conseguir un grado apreciable de resistencia al frío, alcanzándose el máximo resistencia entre 700 y 800 h
Keywords: Capacidad de regeneración de raíces; Olea europaea; Pistacia lentiscus; Quercus ilex; Quercus suber; Resistencia al frío

EVOLUCIÓN TEMPORAL DEL GRADO DE ENDURECIMIENTO DE PLANTAS DE VIVERO DE 4 ESPECIES FORESTALES ESPAÑOLAS CULTIVADAS EN LOCALIDADES CON CONDICIONES CLIMÁTICAS DISTINTAS - Fernández, M.; Carvajal, F.; Alejano, R.; Domínguez, L.; Tapias, R.; Alesso, S. P. (IV Congreso Forestal Español, 2005)
Desde principio del otoño hasta principio de primavera se estudió la evolución de algunos caracteres morfo-fisiológicos indicadores de la calidad de las plantas de vivero destinadas a repoblación forestal (altura, diámetro, distribución de biomasa, nutrición mineral, capacidad de regeneración de raíces y resistencia al frío). Las especies ensayadas fueron Quercus suber, Q. ilex (de dos regiones de procedencia, 11e y 15a), Pistacia lentiscus y Olea europaea var. sylvestris. Todas ellas eran de una savia, procedentes de semillas germinadas en la primavera anterior, crecidas en el mismo tipo de envase (300 cm3) y con el mismo substrato pero cultivadas en dos viveros de localización y características climáticas diferentes. En cuanto al patrón de evolución temporal de los parámetros medidos, se advirtió una alta correlación con la temperatura ambiente, siendo el vivero de clima con estaciones más marcadas el que alcanzó con anterioridad su grado máximo de resistencia al frío y el que retrasó la salida de la dormición durante la época invierno-primavera. Indudablemente, las distintas especies se diferenciaron en su patrón de evolución y en el grado de resistencia al frío conseguido, debiendo resaltar las diferencias encontradas entre las dos procedencias de encina, siendo la de clima con estaciones más extremas (15a) la que en todo momento presentó un mayor grado de resistencia al frío. También se encontró un alto grado de correspondencia entre el contenido en K y la resistencia al frío o el contenido en N y P con la capacidad de regeneración de raíces. Las cuatro especies necesitaron acumular, al menos, 350 h (< 8 ºC) para conseguir un grado apreciable de resistencia al frío, alcanzándose el máximo resistencia entre 700 y 800 h
The following values have no corresponding Zotero field: periodical: IV Congreso Forestal Español pub-location: Zaragoza
Keywords: Capacidad de regeneración de raíces; Olea europaea; Pistacia lentiscus; Quercus ilex; Quercus suber; Resistencia al frío

Seasonal and species-specific response of VOC emissions by Mediterranean woody plant to elevated ozone concentrations - Llusia, J; Penuelas, J; Gimeno, B S (ATMOSPHERIC ENVIRONMENT, 2002)
Although certain factors controlling plant emission rates of volatile organic compounds (VOCs) are reasonably well understood, the influence of elevated ozone concentrations as abiotic stress is mostly unknown. Therefore, we studied the effects of ozone concentrations on seasonal biogenic volatile organic compound (BVOC) emissions by different Mediterranean plant species in open top chambers (OTC). Three ozone treatments were established: filtered air (F), non-filtered air (NF), and fumigated air (NF +) adding 40 nl l(-1) of ozone over NF. We studied the response of VOC emission in saplings of four Mediterranean woody plant species and subspecies: Ceratonia siliqua L., Olea europaea L., Quercus ilex spp. ilex L., and Quercus ilex spp. rotundifolia L. as representative of natural Mediterranean vegetation. No visible symptoms were detected on the leaves. No significant effect was found on net photosynthetic rates or stomatal conductance except for an increase in net photosynthetic rates in Quercus ilex ilex in spring and summer and an overall slight increase in Quercus ilex rotundifolia. Emissions of the total VOCs from Ceratonia siliqua in summer, and from Olea europaea and Quercus ilex rotundifolia in spring increased in ozone fumigated OTC in comparison with F or NF OTC. Decreased emissions were found in Quercus ilex rotundifolia in summer. There were no significant differences between ozone fumigation treatments for the other plant species and seasons. When considering particular VOCs, the results were also variable among species and time of the year. While alpha-pinene emissions decreased with ozone fumigation in Olea europaea, alpha-pinene and limonene emissions increased in Quercus ilex ilex. The responses of these particular VOCs did not always match the responses of total VOCs. In spite of this strong variability, when considering overall annual data for all species and seasons, there were increased net photosynthetic rates (37%) and limonene (95%) and total VOC (45%) emission rates in ozone-fumigated plants, whereas stomatal conductance did not change. Since VOCs are precursors of ozone, the increase in BVOC emission as a consequence of elevated tropospheric ozone concentrations may lead to positive feedback mechanisms in ozone formation. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: biogenic VOCS; Ceratonia siliqua; Olea europaea; Quercus ilex ilex; Quercus ilex rotundifolia; terpenes; tropospheric ozone

Seasonal and species-specific response of VOC emissions by Mediterranean woody plant to elevated ozone concentrations - Llusia, J.; Penuelas, J.; Gimeno, B. S. (ATMOSPHERIC ENVIRONMENT, 2002)
Although certain factors controlling plant emission rates of volatile organic compounds (VOCs) are reasonably well understood, the influence of elevated ozone concentrations as abiotic stress is mostly unknown. Therefore, we studied the effects of ozone concentrations on seasonal biogenic volatile organic compound (BVOC) emissions by different Mediterranean plant species in open top chambers (OTC). Three ozone treatments were established: filtered air (F), non-filtered air (NF), and fumigated air (NF +) adding 40 nl l(-1) of ozone over NF. We studied the response of VOC emission in saplings of four Mediterranean woody plant species and subspecies: Ceratonia siliqua L., Olea europaea L., Quercus ilex spp. ilex L., and Quercus ilex spp. rotundifolia L. as representative of natural Mediterranean vegetation. No visible symptoms were detected on the leaves. No significant effect was found on net photosynthetic rates or stomatal conductance except for an increase in net photosynthetic rates in Quercus ilex ilex in spring and summer and an overall slight increase in Quercus ilex rotundifolia. Emissions of the total VOCs from Ceratonia siliqua in summer, and from Olea europaea and Quercus ilex rotundifolia in spring increased in ozone fumigated OTC in comparison with F or NF OTC. Decreased emissions were found in Quercus ilex rotundifolia in summer. There were no significant differences between ozone fumigation treatments for the other plant species and seasons. When considering particular VOCs, the results were also variable among species and time of the year. While alpha-pinene emissions decreased with ozone fumigation in Olea europaea, alpha-pinene and limonene emissions increased in Quercus ilex ilex. The responses of these particular VOCs did not always match the responses of total VOCs. In spite of this strong variability, when considering overall annual data for all species and seasons, there were increased net photosynthetic rates (37%) and limonene (95%) and total VOC (45%) emission rates in ozone-fumigated plants, whereas stomatal conductance did not change. Since VOCs are precursors of ozone, the increase in BVOC emission as a consequence of elevated tropospheric ozone concentrations may lead to positive feedback mechanisms in ozone formation. (C) 2002 Elsevier Science Ltd. All rights reserved.
The following values have no corresponding Zotero field: pub-location: THE BOULEVARD, LANGFORD LANE, KIDLINGTON, OXFORD OX5 1GB, ENGLAND publisher: PERGAMON-ELSEVIER SCIENCE LTD
Keywords: biogenic VOCS; Ceratonia siliqua; Olea europaea; Quercus ilex ilex; Quercus ilex rotundifolia; terpenes; tropospheric ozone

Differences in the response of carbon assimilation to summer stress (water deficits, high light and temperature) in four Mediterranean tree species - Faria, T; Silvério, D; Breia, E; Cabral, R; Abadía, A; Abadia, J; Pereira, J S; Chaves, M M (Physiologia Plantarum, 1998)
Daily changes in photoprotective mechanisms were studied in sun leaves of Quercus suber L., Quercus ilex L., Olea europaea L. and Eucalyptus globulus Labill. trees during the summer in Portugal. Even though stomatal closure explained most of the diurnal variation in carbon assimilation along the summer, a decline in the photochemical yield of photosystem II (F′v/F′m) also occurred, as a result of an excess of intercepted solar radiation when carbon assimilation is limited by stomatal closure due to high vapour pressure deficits and/or soil water deficits. These changes were accompanied by the conversion of violaxanthin to antheraxanthin and zeaxanthin which were correlated with thermal dissipation of excess photon energy. In spite of a common general response, differences between species were observed -Olea europaea, which is a slow-growing tree, had the lowest net photosynthetic rates, the highest proportion of carotenoids in relation to chlorophyll and the highest rates of de-epoxidation of violaxanthin. This enabled a large thermal dissipation of the excess intercepted radiation but led to rather small values of light utilisation for photochemistry (ca 20%). In contrast, in E. globulus, a fast-growing tree, photosynthetic rates were the highest, thermal dissipation of absorbed radiation the lowest and maximal values of light utilisation for photochemistry reached ca 50%. The two Quercus species exhibited an intermediate response. A high degree of co-ordination is apparent between stomatal behaviour, photosynthetic capacity and photoprotection mechanisms.
Keywords: Energy dissipation; Eucalyptus globulus; Olea europaea; photosynthesis; Quercus ilex; Quercus suber; xanthophyll cycle; zeaxanthin

Polyphenol deposition in leaf hairs of Olea europaea (Oleaceae) and Quercus ilex (Fagaceae) - Karabourniotis, G; Kofidis, G; Fasseas, C; Liakoura, V; Drossopoulos, I (AMERICAN JOURNAL OF BOTANY, 1998)
The subcellular localization (cytoplasm, vacuoles, cell walls) of polyphenol compounds during the development of the multicellular nonglandular leaf hairs of Olea europaea (scales) and Quercus ilex (stellates), was investigated. Hairs of all developmental stages were treated with specific inducers of polyphenol fluorescence, and the bright yellow-green fluorescence of individual hairs was monitored with epifluorescence microscopy. During the early ontogenetic stages, bright fluorescence was emitted from the cytoplasm of the cells composing tie multicellular shield of the scales of O. europaea. Transmission electron micrographs of the same stages showed that these cells possessed poor vacuolation and thin cell walls. The nucleus of these cells may be protected against ultraviolet-B radiation damage. The progressive vacuolation that occurred during maturation was followed by a shifting of the bright green-yellow fluorescence from the perinuclear region and the cytoplasm to the cell walls. The same trends were observed during the development of the nonglandular stellate hairs of Quercus ilex, in which maturation was also accompanied by a considerable secondary thickening of the cell walls. Despite the differences in morphology, high concentrations of polyphenol compounds are initially located mainly in the cytoplasm of the developing nonglandular hairs, and their deposition on the cell walls rakes place during the secondary cell wall thickening. These structural changes during the development of the leaf hairs make them a very effective barrier against abiotic (UV-B radiation) and probably biotic (pathogenic) stresses.
Keywords: cell walls; development; leaf hairs; Olea europaea; phenolics; Quercus ilex; ultraviolet-B radiation damage

Trichome density and its UV-B protective potential are affected by shading and leaf position on the canopy - Liakoura, V.; Stefanou, M.; Manetas, Y. (Environmental and Experimental Botany, 1997)
In Olea europaea trichome density and UV-B absorbing compounds of leaf hairs and the lamina proper of leaves located in south-facing, north-facing and the internal of the canopy were positively correlated to the UV-B midday instant irradiance measured in September at these three different positions of the canopy. The correlation between these three parameters and the receiving photosynthetically active radiation (PAR), however, was weaker. In Quercus ilex, trichome density and its UV-B absorbing capacity were considerably higher in the exposed, south-facing leaves, compared to the deeply shaded ones; the UV-B absorbing capacity of the de-haired lamina, however, was the same. In the broad- leaved, alpine rosette of Verbascum speciosum, one could distinguish two areas on the leaves, one exposed and one shaded by the superimposed lamina. Although trichome density and the UV-B absorbing compounds of the de-haired leaf were the same in the two areas, the UV-B absorbing capacity of hairs was considerably increased in the exposed region. In V. speciosum, exposure induced also qualitative changes in the UV-B absorbance profile, apparently due to the formation of new flavonoid compounds absorbing maximally at 345-350 nm. In all other cases, the differences were mainly quantitative. The results support the postulate of a function of leaf hairs as a UV-B radiation screen and suggest that trichome density and/or its UV-B absorbing capacity may depend on irradiance during leaf development.
Keywords: leaf hairs; Olea europaea; phenolics; Quercus coccifera; Quercus ilex; uv-b radiation; verbascum speciosum

Trichome density and its UV-B protective potential are affected by shading and leaf position on the canopy - Liakoura, V; Stefanou, M; Manetas, Y (Environmental and Experimental Botany, 1997)
In Olea europaea trichome density and UV-B absorbing compounds of leaf hairs and the lamina proper of leaves located in south-facing, north-facing and the internal of the canopy were positively correlated to the UV-B midday instant irradiance measured in September at these three different positions of the canopy. The correlation between these three parameters and the receiving photosynthetically active radiation (PAR), however, was weaker. In Quercus ilex, trichome density and its UV-B absorbing capacity were considerably higher in the exposed, south-facing leaves, compared to the deeply shaded ones; the UV-B absorbing capacity of the de-haired lamina, however, was the same. In the broad- leaved, alpine rosette of Verbascum speciosum, one could distinguish two areas on the leaves, one exposed and one shaded by the superimposed lamina. Although trichome density and the UV-B absorbing compounds of the de-haired leaf were the same in the two areas, the UV-B absorbing capacity of hairs was considerably increased in the exposed region. In V. speciosum, exposure induced also qualitative changes in the UV-B absorbance profile, apparently due to the formation of new flavonoid compounds absorbing maximally at 345-350 nm. In all other cases, the differences were mainly quantitative. The results support the postulate of a function of leaf hairs as a UV-B radiation screen and suggest that trichome density and/or its UV-B absorbing capacity may depend on irradiance during leaf development.
Keywords: leaf hairs; Olea europaea; phenolics; Quercus coccifera; Quercus ilex; uv-b radiation; verbascum speciosum

DRY-MATTER INTAKE PER MOUTHFUL BY GRAZING DAIRY GOATS - PEINADOLUCENA, E; SANCHEZRODRIGUEZ, M; GOMEZCASTRO, A G; MATAMORENO, C; GALLEGOBARRERA, J A (SMALL RUMINANT RESEARCH, 1992)
Mouthful grass intake varied widely from season to season, with minimal values in winter (0.09 g DM) that increased to 0.51 g DM in Spring and decreased in Summer (0.21 g DM). Mouthful intake for shrubby species ranged between lowest for Cistus salvifolius (0.16-0.33 g DM) to C. ladanifer (0.95-3.57 g DM), followed by C. albidus (0.33-1.46 g DM). Quercus rotundifolia was the most frequently ingested arboreal species throughout the year, although the maximum DM content per mouthful (1.58 g) was for Olea europaea. These results show that the greatest weight per mouthful of grass was in spring. The largest amount of DM on a year-round basis was provided by the shrub (C. ladanifer, and the tree O. europaea. Differences in DM intake per mouthful for each species suggest that studies of comparative palatability based on grazing time or number of mouthfuls may lead to errors when estimating actual DM intake for different species studied. Such estimates should be corrected in the light of relative weight per mouthful for each food species.
APS
Keywords: Grazing; Olea europaea; Quercus rotundifolia